2018
DOI: 10.1002/path.5167
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic p27Kip1 promotes tumorigenesis via suppression of RhoB activity

Abstract: The cell cycle inhibitor p27 is a tumor suppressor via the inhibition of CDK complexes in the nucleus. However, p27 also plays other functions in the cell and may acquire oncogenic roles when located in the cytoplasm. Activation of oncogenic pathways such as Ras or PI3K/AKT causes the relocalization of p27 in the cytoplasm where it can promote tumorigenesis by unclear mechanisms. Here, we investigated how cytoplasmic p27 participates in the development of non-small cell lung carcinomas. We provide molecular an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…P27 not only regulates the cell cycle but also suppresses cell proliferation by impacting the formation of the cell cycledependent complex cell division protein kinase 6 (CDK6)/ cyclin D1 (CCND1) (33). When located in the cytoplasm, p27acquires oncogenic roles, and its levels in non-small cell lung carcinoma patients appear to be a powerful prognostic marker (34). The deletion of p27 occurs in the early stage of carcinogenesis, and is related to the aggressiveness and metastasis of liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…P27 not only regulates the cell cycle but also suppresses cell proliferation by impacting the formation of the cell cycledependent complex cell division protein kinase 6 (CDK6)/ cyclin D1 (CCND1) (33). When located in the cytoplasm, p27acquires oncogenic roles, and its levels in non-small cell lung carcinoma patients appear to be a powerful prognostic marker (34). The deletion of p27 occurs in the early stage of carcinogenesis, and is related to the aggressiveness and metastasis of liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Given the association of RhoB and tumorigenesis through multilayered integration with numerous signaling pathways and mechanisms of control, the potential for restoration of RHOB through targeted therapeutics is palpable. Murine studies have demonstrated the potential of RhoB restoration to suppress ovarian cancer xenografts and the chemotherapeutic agent gemcitabine has been shown to act on miR-19a, potentially inhibiting tumor growth by means of RHOB [83,84,85,107,108]. The realm of therapy may even extend into greater exploration of plant derivatives, such as gallic acid and protocatechuic acid, which have been shown to positively modulate RHOB, resulting in suppression of several pathways associated with tumorigenesis and metalloproteinase 2 activity [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of RhoB promoted tumorigenesis in p27 −/− animals, but had no effect in p27 CK− knock-in mice. An additional subset of patients with lung cancer demonstrates both the presence of cytoplasmic p27 and maintained RHOB expression, which was strongly associated with decreased patient survival [107]. Conversely, one study identified a role for RHOB in promotion of metastases in lung adenocarcinoma in a murine model evaluated bony metastasis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…RhoA, RhoB and RhoC have oncogenic effects [1,14]. In addition, RhoB [17,18] and RhoBTBs [5] (mainly as RhoBTB2) may suppress tumors. RhoBTBs expression was reduced or silenced in various tumor types [5].…”
Section: Tumorigenesismentioning
confidence: 99%